Foreign language acquisition of perceptually similar segments: evidence from Lower Sorbian [version 2; peer review: 2 approved] - Phil J. Howson (Open Research Europe, 2024)
Lower Sorbian is a moribund language spoken in Eastern Germany that features a three-way sibilant contrast, /s, ʂ, ɕ/. The vast majority of L1 speakers are above eighty years of age and virtually no young Sorbians learn Lower Sorbian as their first language. There are language revitalization programs in place, but this means that virtually all Lower Sorbian speakers are L2 learners whose first language is German. German, as opposed to Lower Sorbian, has a two-way sibilant contrast, /s, ʃ/. So, Lower Sorbian learners need to acquire a perceptually similar sibilant contrast, /ʂ, ɕ/, that commonly assimilates with a single L1 segment, /ʃ/. The two-to-one assimilation makes acquisition difficult. In this project, I examine the acquisition of the three-way sibilant contrast using ultrasound technology. The ultrasound data revealed that learners in the contemporary context do not produce a distinction between /ʂ, ɕ/ and only learners at an advanced level who had significant exposure to L1 speakers have acquired a three-way sibilant distinction. The findings are put into the context of models of L2 acquisition and generalized implications for foreign language acquisition are discussed.